2006
DOI: 10.1136/bjo.2005.077800
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C augmented glaucoma surgery: evolution of filtering bleb avascularity, transconjunctival oozing, and leaks

Abstract: Aims: To prospectively study the evolution of possible high risk features of conjunctival filtration blebs like avascularity, transconjunctival oozing (TCO), and leaks after mitomycin C (MMC) enhanced glaucoma surgery. Methods: Single observer, 2 year prospective study on bleb characteristics of 125 eyes of 125 consecutive patients who had MMC augmented glaucoma surgery with initially successful filtration. MMC (0.2 mg/ml for 2 minutes in most cases) was applied on the area of the scleral flap before dissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 37 publications
4
90
1
4
Order By: Relevance
“…We believe this is due in part to the suppression of angiogenesis at the wound site by MMC, which is known to have potent antiangiogenic properties (39). While a microvascular network was apparent around the operated site soon after wounding in the control mouse eye, the MMC-treated blebs were characterized by the lack of vasculature which corresponded with similar observations in the clinic (41). The suppression of angiogenesis is, however, a double-edged sword.…”
Section: Discussionsupporting
confidence: 63%
“…We believe this is due in part to the suppression of angiogenesis at the wound site by MMC, which is known to have potent antiangiogenic properties (39). While a microvascular network was apparent around the operated site soon after wounding in the control mouse eye, the MMC-treated blebs were characterized by the lack of vasculature which corresponded with similar observations in the clinic (41). The suppression of angiogenesis is, however, a double-edged sword.…”
Section: Discussionsupporting
confidence: 63%
“…In our experience, MMC can be regarded as an enhancement of the deep sclerectomy IOP-lowering effect without evidence of antimetabolite-related complications (Cillino et al 2005). On the other hand, MMC-augmented glaucoma surgery can be associated with a significantly higher frequency of late bleb leaks (Anand & Atherley 2005;Anand et al 2006). and Gaetano Lodato A detailed database search (Medline and PubMed) failed to show any report on the use of synthetic implant materials as adjuvants in penetrating glaucoma surgery (Jampel et al 2002;Wilkins et al 2005).…”
Section: Introductionmentioning
confidence: 81%
“…24 While there is no reported study of comparison in morphology between DS and trabeculectomy blebs, we have reported that anterior limbal MMC application results in a high frequency of avascular and thinwalled blebs in both DS and trabeculectomy. 34 In trabeculectomy, intensive postoperative management may lead to lower IOPs in the long term. 35 Our postoperative regime for DS, besides topical steroids, consists of subconjunctival 5-FU injections for failing blebs, LGP and needle revision with subconjunctival MMC or 5-FU.…”
Section: Discussionmentioning
confidence: 99%